ANALYSIS OF THE INFLUENCE OF PROFITABILITY, SOLVENCY, AND LIQUIDITY ON AUDIT REPORT LAG WITH COMPANY SIZE AS A MODERATION VARIABLE IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE DURING THE PERIOD 2018-2022 - Imelda, Lia; Ikhsan, Syarbini; Espa, Vitriyan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to examine the influence of profitability, solvency, and liquidity on audit report lag in property and real estate companies listed on the Indonesian Stock Exchange from 2018 to 2022. The population of this study comprised 45 companies, with a sample size of 225 selected through purposive sampling. The criteria for selection included companies that provided complete financial reports and conducted an initial public offering before 2018. Data analysis was performed using SPSS version 25, involving descriptive statistics, classical assumption tests, multiple regression analysis, coefficient of multiple determination, and hypothesis testing. The results reveal that profitability and solvency have a negative impact on audit report lag; liquidity does not affect audit report lag. Company size does not have an effect on profitability on audit report lag; company size affects solvency and has an effect on liquidity on audit report lag.